(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
This paper explores gender perspectives in leadership within higher education, with a focus on how representative leadership can enhance gender inclusion and professional identity. The main goal is to understand how such leadership influences gender-related views and practices in educational settings. The study looks at different leadership styles in the field, highlighting how representative leadership encourages participation across gender, race, ethnicity, and other dimensions, fostering a more inclusive learning environment. Theoretical connections are drawn from representative leadership theory to provide a conceptual framework for this study. Employing a qualitative approach, the researcher follows a phenomenological study with four participants based on primary data from an in-depth interview. This analysis explores representative leadership approaches and their impact on effective school leadership in higher education. In summary, the study highlights the importance of fostering inclusive leadership, adopting effective leadership models, and focusing on gender equity and professional development. These strategies are essential for improving leadership effectiveness, creating equitable educational institutions, and addressing the diverse needs of their communities.